Teknologi Pangan Hewani dalam Wacana Halal dan Haram - Imelda Fajriati (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
The discourse surrounding halal and haram food in Islam remain hot issue among muslims. It is because the difficulty in differentiating the halal from the haram, especially those of meat and fat products in which all related products of pig is forbidden in Islam. There are also many food products which contain forbidden substances so that determining their lawfulness is not an easy feat. The impact of food processing technology which causes this problematic issue is actually can be mitigated if Muslim community are given enough information about technological development in food industry. Physical characteristics of beef and ham can be conveniently determined, among other things by looking at their color, fiber, meat, fat appearance, texture, and scent. Nonetheless, if chemical compound or chemical degraded substances have been processed from pig related substance, such as shortening, gelatin, and fattyacid to be made as food products, its physical characteristics is no longer easy to determine. Thus, to make things clear, chemical examination is the only answer. By doing so, chemical structure of beef and ham can remain detected.